"IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH PADA PAUD DALAM MENDUKUNG MUTU LAYANAN PEMBELAJARAN SEBAGAI FONDASI PENDIDIKAN DASAR: STUDI LITERATUR" - Fahmi; Aisyah Nur Hidayati; Pirda Novalia; Umi Kalsum Nuruljannah; Fahira Salsabilla (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the implementation of School-Based Management (SBM) in early childhood education (PAUD) to improve the quality of learning services. The study employed a qualitative approach using a literature review method, conducted through the collection of secondary data from various sources, such as scientific books, national and international journals, and related documents. Data collection was conducted systematically through a search of relevant and up-to-date literature, then analyzed using descriptive qualitative analysis techniques with a content analysis approach. The results indicate that the implementation of SBM has made a positive contribution to improving the quality of learning services in PAUD. SBM enables educational institutions to manage resources independently, flexibly, and in accordance with the needs of students. Furthermore, SBM also encourages the active participation of various parties, such as teachers, principals, parents, and the community. However, its implementation still faces several obstacles, such as limited human resources, a lack of managerial competence, and limited facilities and infrastructure. Therefore, policy support, improved teacher competency, and ongoing evaluation are needed to ensure optimal implementation of SBM. Thus, SBM is an effective strategy for sustainably improving the quality of PAUD learning services.